DECODING FINANCIAL DISTRESS IN DEVELOPED ECONOMIES: KEY DETERMINANTS AND TRENDS (Contemporary Journal of Social Science Review, 2024)
In the case of developed countries, this study looks at the factors that contribute to financial distress between 2002 and 2021. For empirical analysis, a total of 27 developed economies have been chosen. The explanatory factors in this study include the budget deficit, balance of payments, fiscal and monetary policy, gross domestic products, political instability, corruption, and inflation; the dependent variable is financial distress. A fixed and random effect model has been used to explore the effects of explanatory factors on financial distress. The study showed that balance of payments, fiscal policy, gross domestic product, political instability, and inflation has insignificant effects on financial distress, budget deficit, monetary policy, and corruption have significant effects based on analysis of developed countries. The results show that executing efficient fiscal and monetary policies, keeping a close eye on the budget, managing the balance of payments through market reforms, and all of these things are critical to the growth and development of a nation.